From Text to Image: A Visual Interpretation of Nakirah-Ma’rifah Repetition in QS. Inshirah by @_zukkk - Abd. Basid; Mohammad Fikri Romadhoni; A Rafiq Zainul Mun’im (AL QUDS : Jurnal Studi Alquran dan Hadis, 2025)
QS. Al-Inshirah (94): 5-6 employs a distinctive rhetorical pattern through the repetition of nakirah and ma’rifah, conveying a layered theological message about hardship and relief. This study demonstrates that the shift from al-‘usr in ma’rifah to yusr in nakirah rhetorically affirms the singularity of hardship and the multiplicity of ease, reinforcing a Qur’anic discourse of hope and resilience. Through a semiotic analysis of Zuk’s Qur’an-inspired painting circulated on Instagram, the research further reveals how visual elements—such as light, spatial openness, and symbolic contrast—translate this linguistic meaning into a contemporary visual exegesis. Using a qualitative-descriptive approach that integrates Qur’anic balāghah analysis with Peircean semiotics, the study finds that digital visual interpretations function not merely as aesthetic expressions but as interpretive extensions that recontextualize Qur’anic messages for modern psychological and spiritual concerns. The findings highlight the emergence of visual tafsīr in digital spaces as a significant development in contemporary Qur’anic studies and da’wah, expanding interpretive modalities beyond textual commentary into multimodal meaning-making.